Association between short-term exposure to air pollution and respiratory diseases among children in China: a systematic review and meta-analysis. Issue 11 (2nd November 2022) - Zheng, Junyao; Yang, Xiao; Hu, Siqi; Wang, Yikai; Liu, Jinlin
ABSTRACT: Objective: To assess the quantitative association between short-term exposure to air pollution and respiratory disease outpatient visits among children in China. Methods: We searched articles from 1 January 2000 to 31 December 2020 in six peer-reviewed literature databases following PRISMA guidelines. Results: Of 2668 records, 33 were included in meta-analysis. The pooled excess risks of respiratory disease outpatient visits among children in China per 10 μg/m 3 increase were 0.75% (95% CI: 0.54%, 0.96%) for PM2.5, 0.70% (95% CI: 0.50%, 0.89%) for PM10, 0.82% (95% CI: 0.58%, 1.05%) for SO2, 1.61% (95% CI: 1.25%, 1.98%) for NO2 and 0.74% (95% CI: 0.01%, 1.46%) for O3 . In subgroup analysis, air pollution had a greater impact in southern or central cities, cold seasons, and areas with high relative humidity. Conclusions: Short-term exposure to air pollution was significantly associated with an increased excess risk of respiratory disease outpatient visits among children in China.